2009
DOI: 10.1002/anie.200900277
|View full text |Cite
|
Sign up to set email alerts
|

Polyketide‐Chain Branching by an Enzymatic Michael Addition

Abstract: A new "branch" for polyketide synthases was discovered in the biosynthesis of the antimitotic rhizoxin complex in the endofungal bacterium Burkholderia rhizoxinica. Genetic engineering and the structural elucidation of pathway intermediates revealed that a complex polyketide chain is branched at the beta position by an unprecedented conjugate addition of an acetyl building block to an acryloyl precursor (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 25 publications
3
77
0
2
Order By: Relevance
“…An alternative b-branching mechanism has recently been described by Hertweck and coworkers for the rhizoxin trans-AT PKS [165]. Most rhizoxins, such as 47 or rhizoxin A (13), carry an unusual b-branched d-lactone moiety (Fig.…”
Section: Chain Branching By Michael Addition (B Domains)mentioning
confidence: 96%
See 2 more Smart Citations
“…An alternative b-branching mechanism has recently been described by Hertweck and coworkers for the rhizoxin trans-AT PKS [165]. Most rhizoxins, such as 47 or rhizoxin A (13), carry an unusual b-branched d-lactone moiety (Fig.…”
Section: Chain Branching By Michael Addition (B Domains)mentioning
confidence: 96%
“…To dissect the b-branching process via the same approach as described in Sect. 4.1, the TE domain was inactivated to promote release of individual intermediates [165]. The compounds were identified as the free acids of 60-62, which excluded an isoprenoidlike pathway starting from a b-keto precursor.…”
Section: Chain Branching By Michael Addition (B Domains)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither the expected macrolides nor biosynthetic [38,39] could be detected by LC-HRMS. This finding strongly suggests that the rhi PKS module 1 does not accept heterocycles with nitrogen atoms that do not donate their lone-pair electrons into the ring, regardless of the position(s) and number of the nitrogens.…”
mentioning
confidence: 87%
“…This observation leads us to re-assess the principal role of AHs in PKS assembly lines as housekeeper enzymes, serving to hydrolyse erroneously loaded acetyl groups on ACPs. It should be pointed out that previous work on bacillaene and rhizoxin PKS possessing inactivated terminal thioesterase domains showed that short-and long-chain intermediates were hydrolysed off the PKS in cells [34][35][36] . This finding might be due to an additional proofreading activity present in these pathways, a different activity profile of the cognate AHs, or simply base-catalysed hydrolysis.…”
Section: Please Do Not Adjust Margins Please Do Not Adjust Marginsmentioning
confidence: 99%